2022
DOI: 10.1055/s-0041-1739449
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Cement-Based Carboxymethyl Chitosan/Amorphous Calcium Phosphate

Abstract: Objective This study aimed to analyze, evaluate, and characterize novel cement-based carboxymethyl chitosan/amorphous calcium phosphate (CMC/ACP). Materials and Methods The three cement groups studied were gypsum (Gyp), and CMC/ACP—gypsum cement-based 5% (5% CAG) and 10% (10% CAG). The groups were characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), setting time, and scanning electron microscopy (SEM) data. The characterization results were analyzed qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[21][22][23] CH has desirable characteristics and potential benefits to pulp healing; however, CH has several limitations, such as the fact that it is a crystalline structure arising from solid hydrogen and it has low mechanical strength. 24 It could be blended with HA to provide synergistic effect on the physical and mechanical characteristics. The highest VEGF expression, new blood vessel, and fibroblast cell proliferation on pulp healing were observed in the PC group using CH-HA.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] CH has desirable characteristics and potential benefits to pulp healing; however, CH has several limitations, such as the fact that it is a crystalline structure arising from solid hydrogen and it has low mechanical strength. 24 It could be blended with HA to provide synergistic effect on the physical and mechanical characteristics. The highest VEGF expression, new blood vessel, and fibroblast cell proliferation on pulp healing were observed in the PC group using CH-HA.…”
Section: Discussionmentioning
confidence: 99%
“…It is a cationic polymer that demonstrates good antimicrobial properties. [9][10][11] Composite scaffolds such as chitosan/hydroxyapatite have shown promising osteconductivity, gaining the advantage of both materials used. 12 The effect of hydroxyapatite coated by chitosan nanoparticles and BG nanoparticles on the osteogenic differentiation and proliferation of stem cells of the apical papilla has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It is a cationic polymer that demonstrates good antimicrobial properties. 9 10 11 Composite scaffolds such as chitosan/hydroxyapatite have shown promising osteconductivity, gaining the advantage of both materials used. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the addition of chitosan nanoparticles to ERB sealer did not affect the physical properties of ERB sealer, which exhibited acceptable sealer for obturation material. [11][12][13] However, until now there is deliberation about the appropriate concentration of chitosan nanoparticles, which should be added to sealer. Thus, the purpose of this study was to evaluate the addition of nanoparticle chitosan with concentrations of 0, 10, 20, and 30% to the ERB sealer on its antibacterial and cytotoxicity effect.…”
mentioning
confidence: 99%
“…Previous studies have shown that the addition of chitosan nanoparticles to ERB sealer did not affect the physical properties of ERB sealer, which exhibited acceptable sealer for obturation material. 11 12 13 …”
mentioning
confidence: 99%